Analisa Laju Kegagalan Recloser Untuk Mengurangi Kerugian Akibat Tidak Tersedianya Cadangan Recloser Di PT. Chevron Pacific Indonesia - Riau - Khairul, Ahmad; Nurhalim, Nurhalim (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
In PT. Chevron Pacific Indonesia (PT. CPI), recloser is an important equipment for electric power systems that supposedly able to work optimally in a variety conditions probably happens on the systems. One of the causes of the losses incurred in PT.CPI is because of the recloser failure. Recloser failure is indeed a normal thing to happen, but the problem is when there is a failure (permanent damage) to the recloser which means that they must do the replacement, there is no backup available. This study aims to determine how often the recloser failure occur. So that, by knowing these things and from calculations carried out, will be obtained spare of recloser that must be available in a certain period. And by knowing the spare of recloser, the loss due to unavailability of backup recloser can be minimized and even eliminated.Keywords: recloser, recloser failure, spare recloser